Sensor web - Enabled flood event process detection and instant service. (July 2019) - Du, Wenying; Chen, Nengcheng; Yuan, Sai; Wang, Chao; Huang, Min; Shen, Huanfeng
Abstract: Flood Detection and Service (FD&S) is of great significance to flood management and decision-making. But most of the state-of-art FD&S methods are weak in timeliness and extensibility, and could not reflect flood processes. To resolve the abovementioned problems, this paper proposed the process-based FD&S (PFD&S) method based on Sensor Web. PFD&S is a four-layer architecture the core components of which are the access adapter and process-based detection rules and it is capable of heterogeneous sensor access, flood detection, and flood phase adaptive services. A prototype was developed based on the PFD&S method. Two floods occurring in the Huanghan basin (Hubei, China, with the area of 5.04 × 10 4  km 2 ) during July 2016, was selected as the case studies to validate the PFD&S method and prototype. The results demonstrated that the proposed PFD&S method and prototype could achieve the instant flood process detection and services in 2.7 min. Highlights: The PFD&S method was proposed to achieve the rapid flood process detection and flood phase adaptive services. The PFD&S prototype was designed and implemented based on the PFD&S method. The method and prototype were sensor web - based, with universality and extensibility.